Essentials of Organizational Behavior, Global Edition - Robbins, Stephen P.; Judge, Timothy A. (Pearson International Content, 2025)
Essentials of Organizational Behavior provides the basic core of knowledge in organizational behavior (OB). With complete yet concise coverage, it focuses on translating theory and research into actionable practice. In use at hundreds of colleges and universities worldwide, the text uses relatable scenarios and a conversational style to make lessons engaging, relevant and easy to absorb. The 16th Edition features up-to-date research, discussion and examples of current issues related to all aspects of organizational behavior, including AI, diversity, communication and remote work. This edition also includes new coverage of stress and health in organizations, as well as organizational change.